Effect of sodium bicarbonate and sodium bentonite on digestion and rumen fermentation characteristics of forage sorghum silage-based diets fed to growing steers - K.A. Jacques; D.E. Axe; T.R. Harris; D.L. Harmon (Kansas Agricultural Experiment Station Research Reports, 1985)
One percent sodium bicarbonate (NaHCo3) increased intake of a 50% silage - 50% grain diet, but had no effect on intake of a full-feed sorghum silage diet. The addition of concentrate (rolled milo) slightly lowered rumen pH and decreased acid detergent fiber (ADF) and starch digestion. NaHC03 had no effect on digestibility, but 2% bentonite lowered digestibility of NDF and ADF. Neither compound affected rumen fermentation characteristics.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Sodium bicarbonate; Sodium bentonite; Digestion; Fermentation; Steers; Sorghum silage